Substansi Perubahan Sistem Pemilu Dan Implikasinya Berdasarkan Undang-Undang Nomor 7 Tahun 2017 Tentang Pemilihan Umum Serta RKPD Tahun 2018 Sesuai Permendagri Nomor 32 Tahun 2017 (Pendampingan Bimbingan Teknis Nasional Anggota DPRD Kota Sungai Penuh) - A. H. Rahadian; Resista Vikaliana; Munir Saputra (Institut Ilmu Sosial dan Manajemen Stiami, 2019)
In order to increase the capacity of the Sungai Penuh City Leaders and Members of the DPRD and based on legislation. The Institute for Research and Community Service of the STIAMI Institute of Social Sciences and Management (LPPM - Institut STIAM) Jakarta, has organized National Technical Guidance, in the form of presentations and discussions with the theme: